2020
DOI: 10.1136/bmjnph-2019-000049
|View full text |Cite
|
Sign up to set email alerts
|

Time for nutrition in medical education

Abstract: AimTo synthesise a selection of UK medical students’ and doctors’ views surrounding nutrition in medical education and practice.MethodsInformation was gathered from surveys of medical students and doctors identified between 2015 and 2018 and an evaluation of nutrition teaching in a single UK medical school. Comparative analysis of the findings was undertaken to answer three questions: the perceived importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 21 publications
1
61
0
3
Order By: Relevance
“…Much of medical training is offered as a practical apprenticeship; as such clinical nutrition practice might be improved among students with participatory integrated nutrition curriculum. 15 21 This suggests that medical students would pick up courses more when it is delivered in a more practical manner. This was also evident in the suggestions by students for improving the nutrition content of the curricula which have also been reported in other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of medical training is offered as a practical apprenticeship; as such clinical nutrition practice might be improved among students with participatory integrated nutrition curriculum. 15 21 This suggests that medical students would pick up courses more when it is delivered in a more practical manner. This was also evident in the suggestions by students for improving the nutrition content of the curricula which have also been reported in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Data were collected solely through the administration of a semistructured questionnaire ( online supplementary file 1 ) modified from the Nutritank Medical Students Survey reported by Macaninch et al . 15 The rationale for modifications to the questionnaire was mainly to capture enough and precise information relevant to the goal of our survey. Consequently, the changes were mainly in the form of additions that were not in the original questionnaire but were necessary given the focus of our survey.…”
Section: Methodsmentioning
confidence: 99%
“…For example, a recent UK study found that 71.5% of medical students and 81% of junior doctors had received less than 2 hours of nutrition teaching in the past year; in addition, 85% of students and 91% of doctors stated that they would welcome more nutrition education as part of their training. 3 In our experience, nutrition and other aspects of lifestyle medicine have been neglected in our medical programme. Despite the acknowledgement of lifestyle factors reducing the risk of developing many noncommunicable diseases, specific teaching on this topic has been non-existent in our medical education, forcing us to turn to self-directed learning.…”
Section: W E Commend Keyes Andmentioning
confidence: 99%
“…A recent publication 3 highlights the pressing need for greater education on nutrition within medical curricula. It describes how more than 95% of medical students and doctors believe that doctors play a vital role in nutritional care, yet more than 70% reported that they received less than 2 h nutrition training while at medical school.…”
mentioning
confidence: 99%
“…Barriers to increased medical nutrition education include already-full teaching schedules and limited student engagement, with only 68% of students believing that there is a need for increased nutrition education within their curriculum. 3 In the context of COVID-19, the importance of nutrition has only increased—we must overcome the barriers to greater medical nutrition education to improve the metabolic health of citizens.…”
mentioning
confidence: 99%